Prevalence, Risk Factors, and Clinical Features of Acne Vulgaris: An Observational Study in Secondary Care Hospital - Mulchand Shende; Gayatri Jari; Sushant Chavan; Vaishali Dethe (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Acne is a common skin disorders that troubles and impacts most teenagers and young adults. The objective of this study is to investigate the prevalence, assess risk factors, and analyze the clinical profile of patients presenting with dermatoses, with a particular emphasis on acne vulgaris, in a district general hospital in India. A prospective observational study was conducted on 150 patients diagnosed with acne vulgaris attended the outpatient dermatology department to the district general hospital for six months, reviewing clinical records for demographic data, risk factors, clinical presentation, treatment modalities and acne outcome. Inclusion and exclusion criteria were employed, raw data were analyzed manually. Out of 150 patients, females (53.33%) outnumbered males (46.67%). A high incidence of acne among the population is seen, with the most affected age group being 16-20 years (55.3%). Acne is found more often in those with abnormal menstrual cycles (55%). Sunlight exposure regularly and fewer hours of sleep are linked with acne. Higher incidence is seen in urban groups, and a diet high in glycemic and dairy intake has a high correlation with acne. Polycystic ovarian disease (PCOD), thyroid issues, hormonal imbalance, and polycystic ovary syndrome (PCOS) were prevalent. Increased incidence of acne is found among students and workers between the ages of 25-30 who work in construction and agriculture. Statistically significant association is found between gender and topical corticosteroid usage. Acne is prevalent in adolescents and young adults, particularly females, due to unhealthy diet, hormonal irregularities, inadequate sleep, and misuse of topical corticosteroids.
Keywords: Prevalence; Acne vulgaris; Dermatitis; Observational; Risk factors